Advocacy Services for College Victims of Sexual Assault: Navigating Complicated Confidentiality Concerns. Issue 3 (27th May 2019) - Javorka, McKenzie; Campbell, Rebecca
ABSTRACT: Recent policy reforms related to campus sexual assault may pose confidentiality concerns for victims. The current study aimed to understand current issues in providing confidential advocacy services for college victims of sexual assault, as well as the differential roles that campus-based and community-based advocacy play for college victims. For this qualitative study, semi-structured interviews were conducted with 22 national experts on campus sexual assault from a variety of disciplinary backgrounds. The results indicate that campus-based advocates face challenges in maintaining confidentiality of victims' information, whereas community-based advocates are more likely to have legal confidentiality protections. Consequently, participants noted that an ideal advocacy model for college victims might be one in which campus- and community-based services are closely coordinated to ensure access to services that are both confidential and meet the unique needs of college students. Implications for advocacy services are discussed, as well as future directions for research and evaluation on the effects of evolving policy aimed at improving institutional responses to sexual assault.